Isolation And Optimization Of Culture Conditions For Phb Production By Bacillus Megaterium - MONIKA SHARMA; HARISH KUMAR DHINGRA (International Journal of Pharma and Bio Sciences, 2015)
Poly-β-hydroxybutyrate is an irresistible replacement to petroleum based synthetic plastic, because has mechanical properties similar to polypropylene and completely biodegradable too. In current piece of work, an attempt was made to isolate potent PHB producing bacteria from the different root nodule, soil and water samples. Sudan Black B was used for primary screening of bacterial isolates for PHB production. Presence of functional groups in extracted PHB was confirmed with the help of FITR analysis. Culture media conditions having incubation time period 72 h, temperature 30ËšC, pH 7, glycerol as a carbon source, ammonium sulphate as nitrogen source and C:N ratio as 16:1 were found to be supportive for maximum PHB production by isolate M.Com2(1). Isolate M.Com2(1) (Bacillus megaterium) exhibited significant PHB yield, so that can be exploited for use in industries.